Identification of genetic imbalances in malignant lymphoma using comparative genomic hybridization - Bentz, Martin; Döhner, Hartmut; Werner, Claudius Alexander; Huck, Karin; Baudis, Michael; Joos, Stefan; Lichter, Peter; Schlegelberger, Brigitte; Trümper, Lorenz H.; Pfreundschuh, Michael; Feller, Alfred C.; Möller, Peter (Stem cells, 1995)
In comparison to leukemias, the clinical relevance of chromosomal aberrations in non-Hodgkin's lymphoma (NHL) is not as well understood. This is primarily due to limitations of chromosomal banding techniques which have been the central methods for cytogenetic analysis. These techniques depend on the availability of fresh tumor tissue and the examination of metaphase cells which may not be representative for the major cell clone in vivo. In contrast, the new technique of comparative genomic hybridization (CGH) allows researchers to obtain a comprehensive view of chromosomal gains and losses by analyzing tumor DNA, which can be prepared from archival tissue samples. Results of CGH studies in three different types of lymphoproliferative disorders are outlined in this paper demonstrating that: (1) in chronic B cell leukemias, chromosomal aberrations are missed by banding analysis in a high proportion of cases, (2) CGH on paraffin-embedded tissue samples can be used for cytogenetic analysis within clinical multicenter trials and (3) DNA amplifications are more frequent in NHL than previously assumed. Thus, it can be expected that CGH will contribute both to the understanding of pathogenetic mechanisms and the identification of clinically relevant chromosome aberrations in NHL.